2018
DOI: 10.1371/journal.pone.0194874
|View full text |Cite
|
Sign up to set email alerts
|

Maternal invasion history of Aedes aegypti and Aedes albopictus into the Isthmus of Panama: Implications for the control of emergent viral disease agents

Abstract: Despite an increase in dengue outbreaks and the arrival of chikungunya and Zika disease in Panama, studies on the demographic history of the invasive Aedes mosquitoes that are the principle vectors of these diseases are still lacking in this region. Here, we assess the genetic diversity of these mosquitoes in order to decipher their invasion histories into the Isthmus of Panama. DNA sequences from the mitochondrial cytochrome C oxidase I gene obtained from 30 localities in 10 provinces confirmed the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 50 publications
1
34
0
1
Order By: Relevance
“…samples from Ivory Coast, Nigeria, Cameroon, and Guinea. The levels of nucleotide diversity (π) are similar to values reported in West Africa for both COI and ND4 (Bennett et al, 2016;Paupy et al, 2008), and much lower than the values reported for East Africa (Bennett et al, 2016), America (Eskildsen et al, 2018;Jaimes-Dueñez, Arboleda, Triana-Chávez, & Gómez-Palacio, 2015;Scarpassa, Cardoza, & Cardoso, 2008;Twerdochlib et al, 2012), and Asia (Bosio et al, 2005), possibly due to multiple introduction events in those continents (Bracco, Capurro, Lourenço-de-Oliveira, & Sallum, 2007;Powell & Tabachnick, 2013).…”
Section: West African Originsupporting
confidence: 69%
“…samples from Ivory Coast, Nigeria, Cameroon, and Guinea. The levels of nucleotide diversity (π) are similar to values reported in West Africa for both COI and ND4 (Bennett et al, 2016;Paupy et al, 2008), and much lower than the values reported for East Africa (Bennett et al, 2016), America (Eskildsen et al, 2018;Jaimes-Dueñez, Arboleda, Triana-Chávez, & Gómez-Palacio, 2015;Scarpassa, Cardoza, & Cardoso, 2008;Twerdochlib et al, 2012), and Asia (Bosio et al, 2005), possibly due to multiple introduction events in those continents (Bracco, Capurro, Lourenço-de-Oliveira, & Sallum, 2007;Powell & Tabachnick, 2013).…”
Section: West African Originsupporting
confidence: 69%
“…aegypti throughout numerous regions in its endemic range [14], Ae. albopictus has been spreading throughout Panama for the previous 13 years [12,13]. Our results illustrate that it has not been a key driver of dengue prevalence throughout its time occurring in the country, but that more importantly, there is reason to believe that dengue rates may decrease as the species further proliferates, extirpating Ae.…”
Section: Discussionmentioning
confidence: 85%
“…aegypti is considered resident to Latin America and Panama since the 19 th century, and the primary source of transmission [11] while Ae. albopictus , considered a secondary vector, has been spreading throughout the region ever since it got introduced in Panama in 2004 [12,13]. Widespread extirpation of Ae.…”
Section: Introductionmentioning
confidence: 99%
“…This study uses high-resolution markers to compare patterns of broad-scale genetic structure in Aedes spp. Few such comparative studies have been conducted [37,38], and none have used high-resolution molecular markers, which have demonstrated greater power to distinguish between Aedes populations [39]. We also test landscape genomic hypotheses of isolation by distance [40] and isolation by environment [41]; specifically, whether genetic differentiation is lower between locations with high connectivity to human transportation routes.…”
Section: Introductionmentioning
confidence: 99%